Health risk behaviour among adolescent students in higher secondary school of Kathmandu metropolitan city, Nepal - Shah, Sanjaya Kumar; Duwal, Shree Laxmi; Shah, Richa; Bhatta, Ramesh; Karki, Rajesh; Chaudhary, Anil (International Journal Of Community Medicine And Public Health, 2021)
Background: Health-risk behaviours are those activities that contribute to the leading causes of mortality, morbidity, disability, and social problems among youth and adults, often are established during childhood and adolescence, extend into adulthood, and are interrelated. The objective of the study was to assess health risk behaviours and their influencing factors among adolescent students in higher secondary school of Kathmandu metropolitan city. Methods: The study was a school based cross-sectional quantitative type. The study was conducted in three government schools of Kathmandu metropolitan city, Nepal. The purposive sampling technique was applied to select total 250 respondents from grade 11 and 12. The self-administered questionnaire was used for the data collection. Results: Study shows that majority of respondents were between aged 17-20 years, 62.4% were female and 76.8% from Hindu religion. Out of the total respondents, 6.4% smoked cigarettes, 18.4% drank alcohol and 6.8% used drugs. Regarding Initiation risk behaviour, 25% first smoked, 32.6% first drank alcohol and 11.76% first used drug at age <14 years (pre-adolescence). The major influencing factor for involving health risk behaviours are peer pressure (70.58%) followed by their curiosity (29.42). Likewise, this study revealed highly association between risk behaviours of respondents and peer pressure. Conclusions: Despite the widespread of knowledge about negative effect of health risk behaviours, the prevalence is of smoking, drinking alcohol and drug use is higher. There is urge need of initiation and activities regarding health risk behaviour targeting to preadolescents and adolescents’ students.